1978
DOI: 10.1111/j.1365-2184.1978.tb00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Profile of the Emt6 Cell Cycle In Vitro

Abstract: Simultaneous RNA and DNA estimations were carried out during the cell cycle of EMT6/M/CC cells growing in vitro following synchronization by mitotic selection. the determinations were performed with a flow cytofluorimeter on individual cells stained with acridine orange. It was found that the RNA content increased during G1 then remained virtually constant between early and mid S phase, but a second increase occurred during late S. the rate of uptake of tritiated uridine paralleled these changes in RNA levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This metachromatic property of acridine orange has been used extensively to study the RNA and DNA content of populations of single cells by flow cytometry in many cell systems (4,5,11,14,15). It has also been shown that denatured single-stranded DNA emits red fluorescence in proportion to the degree of DNA denaturation (6).…”
Section: Discussionmentioning
confidence: 99%
“…This metachromatic property of acridine orange has been used extensively to study the RNA and DNA content of populations of single cells by flow cytometry in many cell systems (4,5,11,14,15). It has also been shown that denatured single-stranded DNA emits red fluorescence in proportion to the degree of DNA denaturation (6).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the cells in fractions 1 and 2 lie within the growth fraction whilst the cells in the R fraction are from the inner region of the viable rim. Cells in fraction 3 are from the transitional zone between them, Rapidly dividing EMT6 monolayer cells were reported to have higher cellular RNA content than non-dividing cells (Watson and Chambers, 1978). It is therefore reasonable to suppose that the RNA content of cells in the outer region of the spheroids is higher than that of cells in the inner region.…”
Section: Characteristics Of Cells Ffom Different Fractions Of Spheroidmentioning
confidence: 99%